Effect of Nitric Oxide on the Interaction Between Mitochondrial Malate Dehydrogenase and Citrate Synthase - Yu-chen LIU; Juan WANG; Pei-ying SU; Chun-mei MA; Shu-hua ZHU (Journal of Integrative Agriculture, 2014)
Mitochondrial malate dehydrogenase (mMDH) and citrate synthase (CS) are sequential enzymes in Krebs cycle. mMDH, CS and the complex between mMDH and CS (mMDH+CS) were treated with nitric oxide solution. The roles of notric oxide (NO) on the secondary structures and the interactions between mMDH and CS were studied using circular diehroism (CD) and Fourier transform surface plasmon resonance (FT-SPR), respectivley. The effects of NO on the activities of mMDH, CS and mMDH+CS were also studied. And the regulations by NO on mMDH and CS were simulated by PyMOL software. The results of SPR confirmed that strong interaction between mMDH and CS existed and NO could significantly regulate the interaction between the two enzymes. NO reduced the mass percents of α-helix and increased that of random in mMDH, CS and mMDH+CS. NO increased the activities of CS and mMDH+CS, and inhibited the activity of mMDH. Graphic simulation indicated that covalent bond was formed between NO and Asn242 in active site of CS. However, there was no direct bond between NO and mMDH. The increase in activity of mMDH+CS complex depended mostly on the interaction between NO and CS. All the results suggested that the regulations by NO on the activity and interaction between mMDH and CS were accord with the changes in mMDH, CS and mMDH+CS caused by NO.